Neural Correlates of Causal Inferences in Discourse Understanding and Logical Problem-Solving: A Meta-Analysis Study - Feng, Wangshu; Wang, Weijuan; Liu, Jia; Wang, Zhen; Tian, Lingyun; Fan, Lin (Frontiers in Human Neuroscience, 2021)
During discourse comprehension, we need to draw inferences to make sense of discourse. Previous neuroimaging studies have investigated the neural correlates of causal inferences in discourse understanding. However, their findings have been divergent, and how this type of inferences is related to causal inferences in logical problem solving remains unclear. Hence, using the activation likelihood estimation approach, the current meta-analysis analyzed 19 experiments on causal inferences in discourse understanding and 20 experiments on that in logical problem solving to identify the neural correlates of these two cognitive processes, as well as their shared and distinct neural correlates. We found that causal inferences in discourse comprehension recruited a left-lateralized frontotemporal brain system, including left inferior frontal gyrus, left middle temporal gyrus, and bilateral medial prefrontal cortex, while causal inferences in logical problem solving engaged a non-overlapping brain system in the frontal and parietal cortex, including left inferior frontal gyrus, bilateral middle frontal gyri, dorsal medial prefrontal cortex, and left inferior parietal lobule. Furthermore, the pattern similarity analysis showed that the causal inferences in discourse understanding were primarily related to the terms about language processing and theory-of-mind processing. Both types of inferences were found related to the terms about memory and executive function. These findings suggest that causal inferences in discourse understanding recruit distinct neural bases from that in logical problem solving and relies more on semantic knowledge and social interaction experiences.